Social system design methodology for transitioning to a new social structure – a holistic urban living lab approach to the well-being city - Kimura, Atsunobu; Haraguchi, Hisashi; Yamauchi, Yutaka; Matsuura, Katsuta (Frontiers in Sociology, 2023)
In recent years, along with the rise of new technologies such as AI, IoT, and Bigdata, there has been much discussion replacing entire cities with smart cities. These discussions have given rise to questions about what kind of society should be realized, and keywords such as well-being and sustainability are attracting attention. In this context, how concretely can we transform our current cities into new social structures? Social system design methodology is, in this paper, intend to achieve a comprehensive transition to a new social system, rather than overcoming individual social problems. In Japan, approaches to transforming society, such as elections and social activism, are not fully functional. Transitioning to a new social structure requires critiques from inside together with the presentation of concrete activities. We propose a systematized social system design methodology that aims at a principled transition; it is based on analyses of a series of practices developed in Omuta City, Fukuoka Prefecture in Japan. The methodology proposes a new way of perceiving social systems, practitioner attitude, and a practical design process. It also suggests that existing social system concepts create fundamental problems that lead to discomfort for practitioners, that clarifying existing concepts through policy background analysis can lead to a new view of social system concepts, and that bottom-up practices that realize these new concepts can begin to transform social systems. In order to confirm the versatility of this methodology, two case studies involving care prevention and the work of persons with disabilities are analyzed.